Long-term stability and performance of Cas9/guide RNA-based gene drives in anopheline mosquitoes - Rebeca Carballar-Lejarazú; Yuemei Dong; Thai Binh Pham; Taylor Tushar; Drusilla Stillinger; Devin Ngoc Nguyen; Lorena Winokur; Mihra Tavadia; Mabel Tao; George Dimopoulos; Anthony A. James (Proceedings of the National Academy of Sciences, 2026)
Gene-drive population modification strategies are being developed to control the transmission by anopheline mosquitoes of the parasites that cause human malaria. These approaches are designed to reduce disease prevalence and incidence by spreading dominant antiparasite effector genes throughout vector populations. The strains must sustain drive and parasite suppression properties over extended periods of time to have an epidemiological impact. Three gene-drive strains, AcTP13 and AcTP43 in Anopheles coluzzii and AgTP13 in Anopheles gambiae , carrying autonomous Cas9/guide RNA-based drive systems linked to multiple antiparasite effector genes were remarkably stable in all A. coluzzii replicates over a 2-y (35 generation) period in laboratory cage trials. Two of three A. gambiae replicates performed equally well. Stability was assessed as a function of population dynamics (size), molecular integrity of the gene-drive cassettes, maintenance of drive efficiency (gene conversion), generation and accumulation of mutant drive-resistant target alleles, drive system-generated off-target effects, and effector gene parasite suppression activity. All lines met stability requirements with the exception of one AgTP13 cage replicate that was affected by drive-resistant target-site mutations. Notably, all strains retained parasite suppression activity and high drive efficiencies throughout the duration of the trials. These results support the further development and deployment of these strains for malaria control.